Hospital Ownership and Technical Inefficiency - Burgess, James F.; Wilson, Paul W. (Management Science, 1996)
The theoretical industrial organization literature cites varying factors which might influence the degree of technical efficiency achieved under different ownership structures in the US hospital industry. Unfortunately, this literature offers no consensus regarding the net direction and magnitude of these various effects. This study analyzes the four types of ownership structure in the US hospital industry—private nonprofit, private for-profit, federal, and state and local government. Distance functions are used to measure technical efficiency of hospitals producing multiple outputs relative to other hospitals in the sample, allowing comparisons among the different ownership types.